Application and Performance Improvement of an Optical Power Stabilization System Based on MEMS-LCVR in a SERF Atomic Magnetometer - Yitong Li; Wenfei Zhang; Jianqi Yang; Ying Liu; Yueyang Zhai (Photonics, 2025)
A stabilization method utilizing MEMS technology combined with a liquid crystal variable retarder (LCVR) was developed to enhance fiber laser output power stability and was applied to a spin-exchange relaxation-free (SERF) atomic magnetometer. Comparative experiments demonstrated that the unstabilized laser output exhibited <semantics>2.8%</semantics> power fluctuations over a 500 s period, while the stabilized laser reduced this to <semantics>0.2%</semantics>. Spectral density analysis confirmed suppressed frequency-domain fluctuations, indicating improved robustness against disturbances. Furthermore, the stabilized laser also reduced optical noise in SERF magnetometry, achieving a sensitivity of <semantics>19.2<mspace width="3.33333pt"></mspace>fT/Hz1/2</semantics>. These results validate that the method optimizes both time- and frequency-domain performance, thereby advancing high-precision SERF magnetometry.